DIGITAL NAVIGATION TECHNOLOGIES AND THE EXPERIENCE OF URBAN PLACE - Halegoua, Germaine (AoIR Selected Papers of Internet Research, 2015)
This paper presents empirical analysis of the ways in which digital navigation technology use encourages pedestrians and motor vehicle operators to re-place the unknown, unfamiliar space of the city as an accessible, familiar, bounded place and how this understanding of space allows for a deeper sense of place on the part of digital media users. Although navigation technology non-use is not directly addressed in this paper, I will present some preliminary findings and offer some initial analysis regarding non-use that has been gathered as part of the questionnaire and interview process. The findings presented in this paper asks us to rethink what we know about the use of navigation technologies in urban space and to reconsider how these technologies are integrated into placemaking activities to help users cultivate a sense of place, rather than to diminish one.